Reconnecting Past and Present with Old Photos. Reconstruction of the Church of the Stimmate in Palermo (diségno, 2021)
Perspective restitution from period photos has rarely been used in researches aiming at the reconstruction of past monuments and urban contexts from period photos, due to the approximation that affected the process of restitution developed with pens and rulers. Digital drawing tools decidedly reduce the approximation and allow a straight 3D reconstruction of buildings displayed in a single photographic image. The chosen case study is the Church of the Stimmate in Palermo, demolished at the end of the 19th century for the construction of the Teatro Massimo, the lyric theatre of Palermo. The church was decorated with valuable stucco sculptures that were saved from demolition and are now exhibited at the Oratorio dei Bianchi in Palermo. Three low-quality photos show the stucco sculptures in their original arrangement around two facing niches of the nave, close to the entrance. Perspective restitution and the survey of the sculptures allowed the 3D reconstruction of the niches with the stucco sculptures. Further images and surveys led to the reconstruction of the façade of the church with the annexed monastery and of a nearby city gate that was demolished at the same time.
Keywords: church of the Stimmate; Massimo theater; perspective restitution; 3D reconstruction; equirectangular images